The Northern Ireland Longitudinal Study: Looking at population changes through time. - Lowry, Estelle; Shuttleworth, Ian; Wilgar, Peter; McLoughlin, Catherine; Connell, Emma (International Journal of Population Data Science, 2025)
Objective The Northern Ireland Longitudinal Study (NILS) is a complex administrative data linkage system. Since its launch in 2006, it has expanded in both breadth and depth, allowing the development of new research agendas which deliver insights into the population of Northern Ireland and how their lives have changed over time. Methods The NILS uses a medical card spine to link census and other administrative datasets resulting in a cohort of c515,000 people representing approx. 28% of medical card registrations. It was originally created based on 2001 Census data, and has since undergone subsequent linkages with Census 2011, 1981 (partial), 1991 and most recently Census 2021 data resulting in a rich dataset spanning 40 years. This is bridged by further routine linkages to vital events and the provision of distinct linkage projects (DLP’s) enables opportunities for in depth exploration of health and social care. Results The 2021 Census introduced several new questions, alongside those asked for the second or subsequent time. This offers new opportunities for research topics such as sexual identity, national identity, passports held, religion, demographics, energy-efficient households, and health. We observe an aging population, housing tenure shows considerably higher proportions of shared ownership in later years, and the proportion of those holding a United Kingdom passport only had decreased at the time of the most recent Census. The number of people stating a long-term health condition has also increased. The Census serves as a valuable tool to examine the impact of the past decade, during which society has faced unprecedented events such as Brexit, the global pandemic, and crises in housing and cost-of-living. Conclusions We present an updated cohort profile, showcasing characteristics of the 2021 Census population, alongside highlighting recent research. As part of the wider UK Census Longitudinal Studies, the NILS aligns with the Scottish and ONS Longitudinal Studies, facilitating cross-UK analysis. New remote access arrangements can further widen our user base.